2017
DOI: 10.15406/unoaj.2017.04.00147
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Patients with Chronic Pain

Abstract: Objective: Restricted normal activities associated with chronic pain are well documented. In contrast, there is a paucity of reports regarding the association between chronic pain patients and their sexual function. The aim of the present "snapshot" study was to evaluate the prevalence and severity of sexual dysfunction (SD) in a cohort of patients suffering from chronic pain.Methods: 709 patients with chronic pain completed questionnaires assessing demographics, pain-intensity, disability and severity of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…In a group of individuals with chronic pain, Gruenwald et al [13] looked at the frequency and severity of sexual dysfunction (SD). They came to the conclusion that a large proportion of people with chronic pain had mild to moderate SD.…”
Section: Discussionmentioning
confidence: 99%
“…In a group of individuals with chronic pain, Gruenwald et al [13] looked at the frequency and severity of sexual dysfunction (SD). They came to the conclusion that a large proportion of people with chronic pain had mild to moderate SD.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are interrelated and produce negative effects both in the physiological domain of sexual functioning and in the psychological domain of sexual well-being (Dorado, McDonnell, Edwards, & Lazaridou, 2018). For this reason, sexual dysfunctions are common in patients with chronic pain (Gallach et al, 2018), prevalence of sexual difficulties being almost double that found in non-clinic population of the same age (Gruenwald, Adler, Haddad, Leiba, & Eisenberg, 2017). The main problems related to sexual response are the decreasing in sexual desire, the difficulty experiencing orgasm, lubrication problems and pain during sexual intercourse (Burri, Lachance, & Williams, 2014;Finn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most prevalent problems of women with pain disorders is sexual dysfunction with sexual satisfaction. [ 10 11 ] Sexual satisfaction is believed to be the last stage of sexual function and is defined as a person's pleasant feeling of sexual intercourse free from any pain or discomfort. [ 12 ] Breast is the second sexual organ of a woman; therefore, its severe and cyclic pain can affect sexual function and consequently women's sexual satisfaction.…”
Section: Introductionmentioning
confidence: 99%